MicroRNA 21as a novel biomarker in hepatitis C virus-related hepatocellular carcinoma - Maha Assem Hussein; Amal Fathy Mohammed Radwan; May Mohsen Fawzi; Laila Ahmed Rashed; Eman Hassan Ahmed Ibrahim Saad (SpringerOpen, 2022)
Abstract Background Hepatocellular carcinoma is considered one of the most common cancers occurring in human population all over the world. It became an increasingly threatening malignancy due to both morbidity and mortality. Chronic viral hepatitis B and hepatitis C are two risk factors, which account for 80-90% of all HCC cases worldwide. Alfa Feto protien is used as a tumor marker for HCC diagnosis and prognosis prediction; however, its false negative rate when used alone is as high as 40% for patients with early-stage HCC. AFP levels remain normal in 15-30% of all the patients, even patients with advanced HCC. It has been demonstrated that miRNAs (MicroRNAs) are an important class of non-coding RNAs. They act as tumor oncogenes or suppressors and are involved in the HCC development. MiRNAs are endogenous nucleotides that can be found in intra- and extracellular spaces, such as the blood, urine, and saliva. The study evaluated the miRNA 21 as a novel biomarker in patients with HCV related hepatocellular carcinoma. Results The study was conducted on three groups. Group (1) included 25 patients with liver cirrhosis due to hepatitis C virus infection. Group (2) included 25 patients with hepatocellular carcinoma (HCC) on top of liver cirrhosis due to hepatitis C virus infection. Group (3) included 10 normal control subjects. There was a significant difference in the mean level of miRNA between the three groups with p value < 0.001 with the highest value in group 2 ( 8.28 ± 2.55), then in group1 (5.04 ± 2.11) and the lowest in group 3 (control) (1.02 ± 0.07). MiRNA 21 has a sensitivity of 68% and a specificity of 96%, to differentiate between the liver cirrhosis group and HCC group. Conclusion miRNA 21 can be a promising marker for detection of patients with HCV-related hepatocellular carcinoma, with higher specificity compared to α feto protein; however, its cost is higher.